Menjaga Kesehatan Jasmani dan Rohani dengan Olahraga dalam Persepektif Hadis: Studi Takhrij dan Syarah Hadis - Fursan Ruhbani (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about sports. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about sports in the history of Abu Daud no. 2152. The results and discussion of this study indicate that the status of shahih hadiths that meet the qualifications of maqbul ma'mul bih for practicing Islam. This study concludes that the hadith narrated by Abu Daud no. 2152 is relevant to be used as our concern for the fitness of our bodies in an effort to maintain physical and spiritual health, as well as to develop the field of sports.